Technology-Focused Post-traditional Communitization - Pfadenhauer, Michaela (Teorie vědy / Theory of Science, 2010)
The starting point for the research project pointed out in this article is the assumption that not only ideas, religion and ideologies but also technical connoted consumer goods could be characterized by socio-cultural qualities. The term “socio-cultural” implies cultural potential in the understanding of contextualization in a world of meaning on the one hand and the social potential of integration in posttraditional communities, i. e. small lifeworlds on the other hand. The article argues from a sociological perspective (highly influenced by Erving Goffman’s dramatological approach) viewing not firstly from the society point of view but consequently from that an individual, characterized by natural artificiality (Helmuth Plessner).